In Vitro Assessment Of Antimicrobial Properties Of Malaysia Mangrove Plant (Rhizophora Apiculata) For The Application In Bone Replacement Materials - Sulaiman, Safwan (2012)
The aim of this study is to conduct in vitro assessment of antimicrobial (ATM) properties of Malaysia mangrove plants (Rhizophora Apiculata) barks against human pathogen bacteria for bone replacement application. Tannin extracted from Rhizophora Apiculata barks has shown a very good and significant performance as an ATM agent. In addition, development of hydroxyapatite (HA) composites with enhanced antimicrobial property are potentially attractive in of bone replacement applications. The extraction of tannin using acetone in ratio 1:5, gave practically about 33-35% of raw tannin as an ATM agent. HA/ATM composites with the ATM percentage in the range of 10-50% were used throughout the studies. Antimicrobial activity test was performed by using three human pathogen bacteria which are Staplococcus aeurus, Staplococcus epidermis and Pseudomonas aeruginosa. The disc diffusion test showed the HA/ATM agent was successfully susceptible against these three bacteria. In addition, the mean inhibition zones of antimicrobial activity were increased with the increasing of the ATM percentage in HA/ATM composites from 10 to 50%. Mechanical properties of the HA/ATM composite were also evaluated and the highest mechanical strength was given by HA/ATM composite with 40% ATM (6.65 ± 1 MPa) followed by 30% ATM (5.61 ± 1 MPa) and 50% ATM (5.46 ± 1 MPa). The results showed that the concomitant admixture of ATM to pure HA considerably increased the compressive strength of HA. Besides that, characterization on the morphology and structure of HA/ATM was done by using SEM. The presence of ATM was found to have significant effects in influencing the morphology of HA crystals. The mathematical model of ATM kinetic release was developed based on the drug release system. By refering to the kinetic release result, it has shown the Higuchi’s model is the best-fit model kinetic regarding to the highest R2 value and indicated that the ATM release from HA matrix as a square root of time dependent process based on diffusion process. Moreover, the reaction order for the reaction involved in HA kinetics growth was estimated through the integral method. Zero-order reaction is the best-fit model which showed that the reaction rate of kinetic growth for HA formation is proportional to the incubation time.